McEwan’s and Wright’s Flight from Dunkirk - Bulger, Laura (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
Such elusive concepts as Englishness and Britishness are reinvented in moments of national crisis, when patriotism demands a collective sense of unity and sacrifice to fight the enemy, as in the epic of the British at War, namely in World War II, during the evacuation of the British troops from the Dunkirk beaches, in June 1940. The reconstruction of such a critical moment of British history through fiction is part of a self-conscious attempt not only to question the official historical narrative, but also to reinvent a British identity in a post war post-imperial Britain. The purpose of our paper is to examine how Ian McEwan’s rendition of the Dunkirk retreat, in Part II of Atonement (2002), was adapted to the screen by British film director Joe Wright, taking into account the technical aspects inherent in the transference to a different medium as well as the ideological implications in it. The war section, both in the novel and in the movie, enlarges the personal drama of the protagonist, accused of a crime he did not commit, and rescued from prison to fight in the World War II against his will. The section raises questions about traditional concepts of patriotism, national identity and ultimately about Englishness and Britishness.